2012
DOI: 10.1111/j.1745-6606.2012.01241.x
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Knowledge Scale: An Application of Item Response Theory to the Assessment of Financial Literacy

Abstract: Despite increasing interest in and funding for financial literacy and financial education programs in the private and public sectors, the field of financial literacy still has a major obstacle to overcome: the lack of a widely disseminated measure of financial literacy, developed through rigorous psychometric analyses. In this article, we develop such a measure, focusing specifically on financial knowledge. Using item response theory (IRT), we analyze items from three national surveys, resulting in a psychomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
145
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(176 citation statements)
references
References 24 publications
(48 reference statements)
4
145
0
3
Order By: Relevance
“…The demographic-related patterns seen among college students mirror ones found with adult samples (e.g., Goldsmith, & Goldsmith, 2006;Knoll & Houts, 2012;Lusardi & Mitchell, 2008;Markow & Bagnaschi, 2005;Monticone, 2010;Woodyard & Robb, 2012). Several studies suggested that parents play a major role in their children's financial socialization (Cude et al, 2006;Jorgensen, 2007;Lusardi & Mitchell, 2009), so the similarity should not be surprising.…”
Section: Differences In Financial Literacy On the Basis Of Demographimentioning
confidence: 64%
“…The demographic-related patterns seen among college students mirror ones found with adult samples (e.g., Goldsmith, & Goldsmith, 2006;Knoll & Houts, 2012;Lusardi & Mitchell, 2008;Markow & Bagnaschi, 2005;Monticone, 2010;Woodyard & Robb, 2012). Several studies suggested that parents play a major role in their children's financial socialization (Cude et al, 2006;Jorgensen, 2007;Lusardi & Mitchell, 2009), so the similarity should not be surprising.…”
Section: Differences In Financial Literacy On the Basis Of Demographimentioning
confidence: 64%
“…Researchers also examined potential effects of financial literacy on borrowing behavior (Huston, 2012;Sevim et al, 2012), saving behavior (Huang et al, 2013), inflation expectations (Bruine de Bruin et al, 2010), and financial behavior (Xiao et al, 2014a). Some researchers examined measuring issues of financial literacy, such as its conceptual definition (Remund, 2010), validation of the measures (Knoll and Houts, 2012), its relevance to product design (West, 2012), and consumer ability to correctly answer financial quiz questions (Schmeiser and Seligman, 2013). Researchers also examined financial educators' teaching strategies (Taylor et al, 2012), discussed how to develop a financial literacy component in a liberal art curriculum (Crain and Ragan, 2012), and conducted international comparative studies on financial literacy (Nicolini et al, 2013).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Tendo em vista que não há um instrumento operacional validado que mensure a alfabetização financeira em sua totalidade (Remund, 2010), optou-se pela utilização de uma proxy, seguindo o procedimento adotado por diversos pesquisadores (Aktinson & Messy, 2012;Shim, Xiao, Barber & Lyons, 2009;Shim et al, 2010;Knoll & Houts, 2012), os quais têm, normalmente, avaliado a alfabetização através de fatores. Nesse estudo, a alfabetização financeira é formada pelos seguintes fatores: conhecimento financeiro, comportamento financeiro e atitude financeira.…”
Section: Procedimentos Metodológicosunclassified